Bright Dots and Smart Optical Microscopy to Probe Intracellular Events in Single Cells - Fujita, Hideaki; Zhong, Chongxia; Arai, Satoshi; Suzuki, Madoka (Frontiers in Bioengineering and Biotechnology, 2019)
Probing intracellular events is a key step in developing new biomedical methodologies. Optical microscopy has been one of the best options to observe biological samples at single cell and sub-cellular resolutions. Morphological changes are readily detectable in brightfield images. When stained with fluorescent molecules, distributions of intracellular organelles and biological molecules are made visible using fluorescence microscopes. In addition to these morphological views of cells, optical microscopy can reveal the chemical and physical status of defined intracellular spaces. This review begins with a brief overview of genetically encoded fluorescent probes and small fluorescent chemical dyes. Although these are the most common approaches, probing is also made possible by using tiny materials that are incorporated into cells. When these tiny materials emit enough photons, it is possible to draw conclusions about the environment in which the tiny material resides. Recent advances in these tiny but sufficiently bright fluorescent materials are next reviewed to show their applications in tracking target molecules and in temperature imaging of intracellular spots. The latter section of this review addresses purely optical methods for reading intracellular status without staining with probes. These non-labeling methods are especially essential when biospecimens exposed to nanomaterials are thereafter required for in vivo uses, such as in regenerative medicine.